Word-formation in original and translated English: source language influence on the use of un- and less - Marie-Aude Lefer; Bruno Cartoni (Quaderns de Filologia: Estudis Lingüístics)
This article aims to assess whether the word-formation features of translated language, as opposed to original language, are source language (SL)-dependent or translation-related. To do so, we analyze the use of the -less and un- negative affixes in original English and in English translated from four SL: French, Italian, Dutch and German. Findings based on the Europarl corpus show that the use of -less and un- in translated English is partially SL-dependent.